2020
DOI: 10.1007/s40200-020-00597-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of peripheral neuropathy and associated pain in patients with diabetes mellitus: Evidence from a cross-sectional study

Abstract: Background Diabetic peripheral neuropathy (DPN) is the most common and troublesome complication of diabetes mellitus. It affects almost half the population with diabetes and worsens quality of life of the patient. This study was aimed to determine the prevalence of peripheral neuropathy and associated pain in patients with diabetes mellitus. Methods This was a cross-sectional study conducted over a period of six months. Patient's ≥ 18 years with confirmed diagnosis of diabetes mellitus were included in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Accordingly, the study shows that pharmacist-led interventions using a simple, reliable, and non-invasive tool ( 16 , 18 , 19 ) can play a valuable role in screening and counseling diabetic patients about DPN and its risk factors. Since DPN affects a varying number of patients with diabetes (from 10% to 90%) ( 20 , 21 ), early diagnosis appears to be the best strategy in the care of the diabetic patient. Timely recognition and appropriate interventions hold promise in slowing down or even reversing the early stage of nerve fiber damage in people with diabetes ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the study shows that pharmacist-led interventions using a simple, reliable, and non-invasive tool ( 16 , 18 , 19 ) can play a valuable role in screening and counseling diabetic patients about DPN and its risk factors. Since DPN affects a varying number of patients with diabetes (from 10% to 90%) ( 20 , 21 ), early diagnosis appears to be the best strategy in the care of the diabetic patient. Timely recognition and appropriate interventions hold promise in slowing down or even reversing the early stage of nerve fiber damage in people with diabetes ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the Study of Maastricht [ 30 ] and the systematic review of Ross both et al [ 31 ] did not provide evidence for an association between the components of metabolic syndrome and especially HTN and DPN. Baxi et al also showed no statistically significant association between HTN and DPN [ 32 ]. According to the recent review by Lee et al, there is no indication that the monitoring of HTN prevents the development of DPN [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, more than 40 million people with diabetes live with neuropathy ( Baxi et al, 2020 ). Along with diabetic nephropathy, diabetic cardiomyopathy, and diabetic retinopathy, diabetic neuropathy, is one of the most serious health effects of diabetes.…”
Section: Introductionmentioning
confidence: 99%